Comparision of Accuracy between Multi Implant Impressions While Using Different Splinting and Impression Materials: An In Vitro Study - Pragya Bali; Farhat Jabeen; Poonam Pathania; Harsh Bali; Shivangi Bali (New Ideas Concerning Science and Technology Vol. 10, 2021)
Statement of Problem: Movement of impression copings inside the impression materials prevents transfer of the 3-dimensional spatial orientation of intra-oral position of implant fixtures to the working cast. .So for the long term success of implant an accurate and passive operation is required. Purpose: This in vitro study evaluated the accuracy of the master cast using different splinting and impression materials. Methodology: A reference mandibular model with 4 internal connection implants was fabricated. Thirty six custom trays were fabricated using autoplymerizing resin. Polyether and poly vinyl siloxane impression material were used. These trays were randomly divided between the two groups, with eighteen trays in each group. Impression techniques were divided into two groups namely: Group I: Direct impression technique with open tray impression copings splinted with auto polymerizing acrylic resin (GC pattern resin). Group II: Direct impression technique with open tray impression copings splinted with Pro-temp TM 4 (bis-GMA) syringable temporization material. Thus, final impressions were made. Master casts were fabricated and evaluated using profile projector. These measurements were compared to the measurements calculated on the reference mandibular model which served as control. Data were analyzed with a one way analysis of variance at a =.00, followed by post hoc Tukey’s test (a=.00). Results: Statistical comparisons were made using ANOVA test and post-hoc test. Same amount of deviation values obtained with resin splinted and bis-GMA splinted impression copings. There was a significant difference in- while using Polyether and poly vinyl siloxane as impression material. Conclusion: The master cast obtained by both the splinting material exhibited no difference from the reference model. In the direct technique, polyether showed better results in terms of accuracy. Splinting provided more accuracy of transfer in multiple abutments using both the impression materials included in the study. Both splinting materials showed comparable amount of deviation from the reference model, any one of the material based on the ease of handling, time consumption, technique sensitivity and availability can be chosen.